Does governance in information technology matter when it comes to organizational performance in Pakistani public sector organizations? Mediating effect of innovation - Amamat, A.; Iqbal, S.; Haider, S. A.; Tehseen, Shehnaz *; Anwar, B.; Mariam, S.; Khalid, R. (Sagepub, 2021)
Information technology governance (ITG) is recognized as a vital organizational ability to exploit opportunities for innovation and enhance organizational performance. However, the potential of ITG for public sector innovation and performance has not been fully grasped in Pakistani public sector organizations (PakPSOs). This study has presented an explanatory model to investigate the mediating effect of innovation in the relationship between ITG and organizational performance in PakPSOs. Partial least squares structural equation modeling (PLS-SEM)–based hierarchical component modeling approach has applied to analyze the model by taking sample data from 97 PakPSOs. The results revealed that ITG positively affected innovation and organizational performance. Innovation positively affected organizational performance. Innovation partially mediated the relationship between ITG and organizational performance. The study corroborates the strategic use of information technology (IT) to enhance innovation and organizational performance in this context. The study contributes to the existing knowledge base through a new theoretical model and promotes academic rigor. The results are also significant for the practice as they can help to achieve organizational performance in terms of operational efficiency, transparency in costs and results, planning and decision making, performance monitoring and control, and collaboration and synergy. The other countries operating in a similar environment can also take the benefit of this study.